The Relationship Between Postpartum Mothers' Knowledge About Breast Care and The Incidence of Breast Milk Dam in Postpartum Mothers Days 3-6 in The Bps Area Mrs. Titik Ekawati, S.St Ds. Kintelan Kec. Puri Kab. Mojokerto - Titiek Idayanti; Rahma Fauziyah; Widya Anggraeni (Kirana Publisher (KNPub), 2024)
The emergence of dam milk at days 3-6 due to a lack of knowledge about the treatment of post partum mothers the right breast. The purpose of this study was conducted to know the relationship of maternal knowledge about postpartum care with the incidence of breast milk dam on postpartum days 3-6 in Region Connecticut District Puri Ny.Titik Ekawati, S.ST Village Kintelan Mojokerto regency. The design of this study using a cross sectional analytic methods. Its population is around 3-6 days post partum mothers who are in the BPS Ny.Titik Ekawati,S.ST the sample was 13 respondents residing in the territory of BPS Ny.Ekawati,S.ST, sampling is the accidental sampling technique, a variable of this study is the independent variable